Base-promoted isomerization of CF3-containing allylic alcohols to the corresponding saturated ketones under metal-free conditions - Hamada, Yoko; Kawasaki-Takasuka, Tomoko; Yamazaki, Takashi (Beilstein Journal of Organic Chemistry, 2017)
Following to the computational expectation, our previously reported intriguing 1,3-proton shift of 4,4,4-trifluorobut-2-yn-1-ols was successfully extended to the 4,4,4-trifluorobut-2-en-1-ol system under metal-free conditions to afford the corresponding saturated ketones in high to excellent chemical yields using such a convenient and easy-to-handle base as DBU at the toluene refluxing temperature, and utilization of the corresponding optically active substrates unambiguously demonstrated that this transformation proceeded in a highly stereoselective fashion.
Keywords: allylic alcohols; chirality; computation; 1,3-proton shift; trifluoromethyl